Base promoted regioselective aromatization for the preparation of substituted 3‐hydroxybenzene dicarboxylate. (3rd June 2020) - Guo, Weihang; Wang, Xianheng; Zhao, Changkuo; Wang, Yuhe
Abstract: A new convenient base promoted aromatization process has been developed to prepare substituted 3‐hydroxybenzene dicarboxylate using commercially available materials. In particular, regioselectivity will occur for substrates with mono‐substitution at 5‐ or 6‐position. This new process provides less reaction steps and moderate yields, and can be used extensively in the synthesis of other substrates to functionalize phenol esters. Abstract :